PENGARUH INOVASI, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP MINAT PEMBELIAN ULANG MIE KASUKA DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Muhammad Nur Fadillah; Eka Ludiya (ITB AAS Indonesia Surakarta, 2024)
The purpose of this research was to examine innovation, product quality and perceived price on repurchase intention with customer satisfaction as an intervening variabel. The method used in this research is descriptive quantitive. The analysis used in this research was test of validity, test of reability, classical assumption test and sobel test. Population in this research was customer of mie kasuka and sample used was 100. Data processing was carried out using the Statistical Program of Science (SPSS). The result innovation can’t influence on repurchase intention and custumer satisfaction. Product quality positive influence on repurchase intention and custumer satisfaction, price perceived positive influence on repurchase intention but can’t influence on customer satisfaction. Custumer satisfaction positive influence product quality on repurchase intention, but can’t influence innovation and price received on repurchase intention